PENGETAHUAN DAN KETERAMPILAN BIDAN DALAM PENANGANAN AWAL PREEKLAMSI SEBELUM DAN SESUDAH PELATIHAN - Juana Linda Simbolon; Sulastry Pakpahan (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
The aim of this study was to determine the differences in the level of knowledge and skills of midwives in the early management of pre-eclampsia in pregnancy